1999
DOI: 10.1016/s0002-9270(99)00007-6
|View full text |Cite
|
Sign up to set email alerts
|

Racial factors and the risk of chronic pancreatitis

Abstract: In comparison with white patients, black patients are two to three times more likely to be hospitalized for chronic pancreatitis than alcoholic cirrhosis. This highly significant (p < 0.001) difference was observed in both men and women: in three different hospitals, and in two different countries. The explanation is unknown, but could be related to racial differences in diet, type or quantity of alcohol consumption, smoking, or ability to detoxify substances harmful to the liver or pancreas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 20 publications
0
11
0
Order By: Relevance
“…However, only a minority of alcoholics develop these diseases [1,4,5,7,8] ; this together with the requirement of several years of ethanol intake, racial factors [39] , and the difficulty of developing adequate experimental models have led to the consideration of other associated etiological factors [26] . The presence of a common etiological factor, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…However, only a minority of alcoholics develop these diseases [1,4,5,7,8] ; this together with the requirement of several years of ethanol intake, racial factors [39] , and the difficulty of developing adequate experimental models have led to the consideration of other associated etiological factors [26] . The presence of a common etiological factor, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…40 Earlier studies have shown that in comparison with White patients, Black patients are 2-3 times more likely to be hospitalised for chronic pancreatitis than alcoholic cirrhosis. 41 Thus, alcoholics in India may be more susceptible to chronic pancreatitis due to a combination of factors such as genetic makeup, racial difference in diet, type or quantity of alcohol, or smoking, etc. Although the present knowledge suggests that ACP patients are likely to have higher interactions with environmental factors in comparison with other types of chronic pancreatitis, there is a strong genetic basis for ACP patients in India.…”
Section: Discussionmentioning
confidence: 99%
“…One third of alcoholic patients with recurrent acute pancreatitis did not progress towards chronic calcifying pancreatitis during an observation period of 11.7 8 5.8 years [15] . Fourth, differences in racial susceptibility may exist since black patients are 2-3 times more likely to be hospitalized for pancreatitis than white patients [16] . These observations demonstrate a marked heterogeneity in susceptibility to chronic alcoholic pancreatitis.…”
Section: Alcohol Consumption and Pancreatitismentioning
confidence: 99%